1992
DOI: 10.1002/art.1780350608
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional similarities between 5‐azacytidine‐treated t cells and a t cell subset in patients with active systemic lupus erythematosus

Abstract: Objective. Antigen-specific CD4+ T cells treated with DNA methylation inhibitors become autoreactive, suggesting a novel mechanism for autoimmunity. To test whether this mechanism might be involved in systemic lupus erythematosus (SLE), phenotypic markers for the autoreactive cells were sought.Methods. Cloned normal T cells were treated with the DNA methylation inhibitor 5-azacytidine (5-azaC) and studied for altered gene expression. T cells from patients with active SLE were then studied for a similar change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
159
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 51 publications
6
159
0
Order By: Relevance
“…The expression of CD11a has previously been reported to be methylation-sensitive in both mouse and human T cells. 15,23,31 To confirm that the expression of CD70 is also methylation-sensitive in mouse T cells, wild-type mouse spleen cells were stimulated with Con-A overnight, and then incubated with or without the DNA methylation inhibitor 5-azacytidine (5 μM) in interleukin 2 (IL-2; 50 U ml −1 ) containing culture media for an additional 72 h. T cells were isolated and the expression of CD70 measured by real-time RT-PCR. We found that CD70 expression increased with 5-azacytidine treatment in wild-type mouse T cells (1.18 ± 0.26 to 5.12 ± 0.84 (mean ± s.e.m.…”
Section: Generation Of Transgenic Micementioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CD11a has previously been reported to be methylation-sensitive in both mouse and human T cells. 15,23,31 To confirm that the expression of CD70 is also methylation-sensitive in mouse T cells, wild-type mouse spleen cells were stimulated with Con-A overnight, and then incubated with or without the DNA methylation inhibitor 5-azacytidine (5 μM) in interleukin 2 (IL-2; 50 U ml −1 ) containing culture media for an additional 72 h. T cells were isolated and the expression of CD70 measured by real-time RT-PCR. We found that CD70 expression increased with 5-azacytidine treatment in wild-type mouse T cells (1.18 ± 0.26 to 5.12 ± 0.84 (mean ± s.e.m.…”
Section: Generation Of Transgenic Micementioning
confidence: 99%
“…14 Hypomethylated, autoreactive CD4+ cells also spontaneously kill autologous macrophages (Mø), causing release of antigenic nucleosomes through mechanisms including demethylation and subsequent overexpression of the PRF1 (perforin) gene. [15][16][17] The hypomethylated cells also overstimulate autologous B-cell antibody production, due to demethylation and overexpression of the genes encoding CD70 (TNFSF7), and CD40L (CD40LG). 18,19 Importantly, procainamide and hydralazine, which cause anti-nuclear antibodies in a majority of people and a lupus-like disease in a subset, are DNA methylation inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the CD11a/CD54 interaction in SLE is further emphasized by observations that CD11a and CD54 expression is significantly increased on peripheral blood lymphocytes from patients with SLE [57,58]. Additionally, CD11a expression is relatively increased on T cells from SLE patients, which correlates with disease activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…T cells from lupus patients may kill autologous monocytes/macrophages, and may thus contribute to both increase of the amount of antigenic apoptotic material and the reduction of its clearance [13,14].…”
Section: Introductionmentioning
confidence: 99%